Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Step-by-step explanation:
[tex]\large\underline{\sf{Solution-}}[/tex]
Given expression is
[tex]\rm :\longmapsto\:tan75\degree + cot75\degree [/tex]
Consider
[tex]\rm :\longmapsto\:tan75\degree [/tex]
[tex]\rm \: = \: tan(45\degree + 30\degree )[/tex]
[tex]\rm \: = \: \dfrac{tan45\degree + tan30\degree }{1 - tan45\degree \times tan30\degree } [/tex]
[tex]\rm \: = \: \dfrac{1 + \dfrac{1}{ \sqrt{3} } }{1 - 1 \times \dfrac{1}{ \sqrt{3} } } [/tex]
[tex]\rm \: = \: \dfrac{1 + \dfrac{1}{ \sqrt{3} } }{1 - \dfrac{1}{ \sqrt{3} } } [/tex]
[tex]\rm \: = \: \dfrac{ \sqrt{3} + 1 }{ \sqrt{3} - 1} [/tex]
On rationalizing the denominator, we get
[tex]\rm \: = \: \dfrac{ \sqrt{3} + 1 }{ \sqrt{3} - 1} \times \dfrac{ \sqrt{3} + 1 }{ \sqrt{3} + 1 } [/tex]
[tex]\rm \: = \: \dfrac{ {( \sqrt{3} + 1)}^{2} }{ {( \sqrt{3}) }^{2} - {(1)}^{2} } [/tex]
[tex]\rm \: = \: \dfrac{3 + 1 + 2 \sqrt{3} }{3 - 1} [/tex]
[tex]\rm \: = \: \dfrac{4+ 2 \sqrt{3} }{2} [/tex]
[tex]\rm \: = \: \dfrac{2(2+ \sqrt{3} )}{2} [/tex]
[tex]\rm \: = \: 2 + \sqrt{3} [/tex]
[tex]\rm\implies \:\boxed{\tt{ tan75\degree = 2 + \sqrt{3} \: }}[/tex]
Now,
[tex]\rm :\longmapsto\:cot75\degree [/tex]
[tex]\rm \: = \: \dfrac{1}{tan75\degree } [/tex]
[tex]\rm \: = \: \dfrac{1}{2 + \sqrt{3} } [/tex]
On rationalizing the denominator, we get
[tex]\rm \: = \: \dfrac{1}{2 + \sqrt{3} } \times \dfrac{2 - \sqrt{3} }{2 - \sqrt{3} } [/tex]
[tex]\rm \: = \: \dfrac{2 - \sqrt{3} }{ {(2)}^{2} - {( \sqrt{3}) }^{2} } [/tex]
[tex]\rm \: = \: \dfrac{2 - \sqrt{3} }{4 - 3} [/tex]
[tex]\rm \: = \: 2 - \sqrt{3} [/tex]
[tex]\bf\implies \:\boxed{\tt{ cot75\degree = 2 - \sqrt{3} \: }}[/tex]
Now, Consider
[tex]\rm :\longmapsto\:tan75\degree + cot75\degree [/tex]
[tex]\rm \: = \: 2 + \sqrt{3} + 2 - \sqrt{3} [/tex]
[tex]\rm \: = \: 4[/tex]
Hence,
[tex]\rm\implies \:\boxed{\tt{ tan75\degree + cot75\degree = 4 \: }}[/tex]
▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬
Alternative Method
[tex]\rm :\longmapsto\:tan75\degree + cot75\degree [/tex]
[tex]\rm \: = \: tan75\degree + \dfrac{1}{tan75\degree } [/tex]
[tex]\rm \: = \: \dfrac{ {tan}^{2}75\degree + 1}{tan75\degree } [/tex]
[tex]\rm \: = \: \dfrac{1}{\dfrac{tan75\degree }{1 + {tan}^{2} 75\degree } } [/tex]
[tex]\rm \: = \: \dfrac{2}{\dfrac{2tan75\degree }{1 + {tan}^{2} 75\degree } } [/tex]
We know,
[tex]\rm :\longmapsto\:\boxed{\tt{ \frac{2tanx}{1 + {tan}^{2} x} = sin2x}}[/tex]
[tex]\rm \: = \: \dfrac{2}{sin150\degree } [/tex]
[tex]\rm \: = \: \dfrac{2}{sin(180\degree - 30\degree )} [/tex]
[tex]\rm \: = \: \dfrac{2}{sin30\degree } [/tex]
[tex]\rm \: = \: 2 \times 2[/tex]
[tex]\rm \: = \: 4[/tex]
Hence,
[tex]\rm\implies \:\boxed{\tt{ tan75\degree + cot75\degree = 4 \: }}[/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.